2017
DOI: 10.1186/s13068-017-0970-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel GH10 xylanase from Penicillium sp. accelerates saccharification of alkaline-pretreated bagasse by an enzyme from recombinant Trichoderma reesei expressing Aspergillus β-glucosidase

Abstract: Background Trichoderma reesei is considered a candidate fungal enzyme producer for the economic saccharification of cellulosic biomass. However, performance of the saccharifying enzymes produced by T. reesei is insufficient. Therefore, many attempts have been made to improve its performance by heterologous protein expression. In this study, to increase the conversion efficiency of alkaline-pretreated bagasse to sugars, we conducted screening of biomass-degrading enzymes that showed synergistic effects with enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
(63 reference statements)
3
12
0
3
Order By: Relevance
“…As previously reported [22], Xyn10 demonstrated a higher activity than Xyn III against alkali-pretreated sugarcane bagasse powder (Fig. 1), reconfirming the excellent performance of Xyn10.…”
Section: Xylanase Activity: Effect Of Labelingsupporting
confidence: 86%
See 3 more Smart Citations
“…As previously reported [22], Xyn10 demonstrated a higher activity than Xyn III against alkali-pretreated sugarcane bagasse powder (Fig. 1), reconfirming the excellent performance of Xyn10.…”
Section: Xylanase Activity: Effect Of Labelingsupporting
confidence: 86%
“…Xyn III of T. reesei was reported to be initially devoid of a CBM and Xyn III, expressed with a xylan-binding domain from Streptomyces olivaceoviridis E-86, showed higher adsorption toward insoluble xylan by a factor of two [28]. Furthermore, when Xyn10 that initially possessed a CBM [22] was modified to be devoid of a CBM, Xyn10 was no longer observed to adsorb onto the substrates (data not shown). Therefore, the CBM of xylanase was found to be critical for the interaction with xylan molecules that are closely associated with cellulose molecules at the substrate surface, which may improve the total activity of the cellulase system toward biomass.…”
Section: Time-lapse Analysis Of Individual Enzymesmentioning
confidence: 96%
See 2 more Smart Citations
“…G0SBF1 is a special xylanase with CBM1. A study showed that the CBM1 of PspXyn10 could bind to cellulose [50]. Therefore, it was hypothesized that the CBM1 of G0SBF1 could bind to the surface of cellulose.…”
Section: Temporal Changes In Secretomes Induced By Arabinose and MCCmentioning
confidence: 99%